Lernen als Lebensthema für alle – Anforderungen an eine weitsichtige Bildungspolitik - Christina Boll; Susanne Kuger; Birgit Reißig (Wirtschaftsdienst, 2025)
– We discuss the importance of a sustainable education policy for the prosperity and stability of society. Early childhood education, schools and vocational training must all be seen as a lifelong learning project in order to promote equal opportunities. Despite the expansion of day care centres and schools, inequalities in access to education persist, especially for children from disadvantaged backgrounds. Vocational education and training is under pressure as the number of trainees is falling and there are matching problems. Education policy must therefore be inclusive in order to open up educational and career opportunities for all.
Keywords: I20; I24; I25; 330; Bildungspolitik; Lernen; Deutschland; Bildungspolitik; Lernen; Deutschland